2002
DOI: 10.1051/0004-6361:20020710
|View full text |Cite
|
Sign up to set email alerts
|

CH3OH and H2O masers in high-mass star-forming regions

Abstract: Abstract. We present a comparison of Class  CH 3 OH (6.7 GHz) and H 2 O (22.2 GHz) masers at high spatial resolution in a sample of 29 massive star-forming regions. Absolute positions of both maser types are compared with mm dust continuum, cm continuum and mid-infrared sources. All maser features -regardless of the species -are associated with massive mm cores, but only 3 out of 18 CH 3 OH masers and 6 out of 22 H 2 O masers are associated with cm emission likely indicating the presence of a recently ignite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
280
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(300 citation statements)
references
References 27 publications
17
280
2
1
Order By: Relevance
“…We know that source evolution and variability play a major role in the detection statistics, however, neither of these are well enough understood at present to be able to account for them explicitly. Our results are also consistent with previous searches for water masers by Beuther et al (2002); Szymczak et al (2005); Xu et al (2008);Breen et al (2010a).…”
Section: Mmb Targetsupporting
confidence: 94%
“…We know that source evolution and variability play a major role in the detection statistics, however, neither of these are well enough understood at present to be able to account for them explicitly. Our results are also consistent with previous searches for water masers by Beuther et al (2002); Szymczak et al (2005); Xu et al (2008);Breen et al (2010a).…”
Section: Mmb Targetsupporting
confidence: 94%
“…We confirmed their estimation, finding that the visual extinction for 13-s is A v ∼ 2700 (see Table 2). Source 13-s is in an early stage of evolution, according to its NIR excess and the presence of H 2 O and Class ii CH 3 OH masers (Beuther et al 2002d), although the detection of a VLA 3.6 cm source at its position (Sridharan et al 2002), suggests that there is a recently ignited protostar that has already formed an ultracompact or hypercompact Hii region, the detected radio emission being consistent with an ionizing B2 V star (Martín-Hernández et al 2008;Qiu et al 2008;Panagia 1973).…”
Section: Continuum Sourcesmentioning
confidence: 96%
“…It is a very active star-forming site, with sources detected from X-rays down to radio wavelengths. It has H 2 O and CH 3 OH maser emission (Sridharan et al 2002;Beuther et al 2002d) and X-ray sources (Beuther et al 2002a), indicating that there is ongoing formation of intermediate-to-high mass stars. The region is embedded within a cluster of over 800 components detected at NIR wavelengths (Martín-Hernández et al 2008;Qiu et al 2008), and it has a rich and energetic outflow component with multiple outflows detected in CO (Beuther et al 2002c(Beuther et al , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has focused on follow-up studies of bright IR sources detected by the Infrared Astronomy Satellite (IRAS) and showing far-infrared (FIR) colors typical of ultra-compact H ii regions (Wood & Churchwell 1989), e.g., in high-density molecular tracers (Bronfman et al 1996;Molinari et al 1996), dust continuum emission , or maser emission (e.g., Palla et al 1993;Beuther et al 2002). While some studies have revealed a few massive cold cores in the neighborhood of the central compact H ii region (e.g., Garay et al 2004), they were mostly biased against the earliest, possibly coldest phases of massive star formation.…”
Section: Article Published By Edp Sciencesmentioning
confidence: 99%